Home work [compact disc, unabridged] : a memoir of my Hollywood years - Andrews, Julie; Hamilton, Emma Walton (Hachette Audio, 2019)
The actor reflects on her Hollywood career; the creations of three of her most iconic films, "Mary Poppins," "The Sound of Music," and "Victor/Victoria"; and her efforts to juggle marriage, children, and fame.